Kolaborasi Nilai-Nilai Pendidikan Agama Islam pada Mata Pelajaran Produktif pada SMK Negeri 4 Kepahiang - Sanjaya Putra; Zubaedi Zubaedi; Nurhidayat Nurhidayat (Journal on Education, 2023)
The purpose of this study was to describe the collaboration of Islamic Religious Education values ​​in Productive Subjects at SMK Negeri 4 Kepahiang, how to plan the implementation and evaluation of the collaboration of Islamic Religious Education values ​​in Productive Subjects. The researcher uses a qualitative approach with a qualitative descriptive method to describe and to reveal the problem in depth and comprehensively. Data collection techniques using observation, interviews, documentation. From the results of this study it was found that the values ​​of Islamic Religious Education that were collaborated in Productive Subjects were Aqidah and Ahlak. follow this program. The inhibiting factors in this collaboration are: there is no collaboration of other subjects at SMK Negei 4 Kepahiang, the application of collaborative PAI values ​​in Productive Subjects has only been carried out or programmed in the Light Vehicle Engineering department